VISUAL MIND MAPPING FOR PRACTICING FOREIGN LANGUAGE SPEAKING - Holovko, Iryna (European Science, 2024)
The paper examines the concept of Visual Mind Mapping technology for practicing foreign language speaking. The main approaches of scientists to the definition of Visual Mind Mapping concept are reviewed. The practice of using mind maps to develop and mast